The elements of library research: What every student needs to know - George, Mary W (Princeton reference, 2008)
This short, practical book introduces students to the important components of the information-seeking process. Unlike guides that describe the research process but do not explain its logic, this book focuses entirely on basic concepts, strategies, tools, and tactics for research--in both electronic and print formats. --from publisher description.